Asynchronous Teledermatology: Experience During the Covid-19 Pandemic in Chile Between 2020 and 2021 [Teledermatología Asincrónica: Experiencia Durante la Pandemia Covid-19 en Chile Entre 2020 y 2021 - Soto-Madrid, D (Ediciones Doyma, S.L., 2023)
Introduction: During the COVID-19 pandemic, face-to-face dermatological care was affected by isolation measures, while the demand for remote dermatological consultations increased. In this context, Dermaonline® arises, an asynchronous teledermatology Project. The aim of this study is to understand how the demand for teledermatology consultations behaved throughout the country and what were the most frequent reasons for consultation during the COVID-19 pandemic between 2020 and 2021. Methods: Retrospective analysis of the data record of the care provided in Dermaonline®, between 2020 and 2021. Results: During the study period, 1,114 teledermatology services were performed, of which 52% were performed from regions other than the metropolitan. The average age was 27 years and the most frequent reason for consultation was “pimples” (48%). Inquiries for “pimples” experienced an overall increase throughout the period. Discussion: Teledermatology was a very useful tool in our country during the COVID-19 pandemic between 2020 and 2021, where distancing measures and the use of personal protection elements, such as masks, were extreme. Probably the foregoing was what determined an increase in the demand for remote dermatological consultations, mainly due to acne or related pathologies. During the period studied, it was possible to respond to more than 1,000 patients with skin problems, with a wide geographical coverage, which demonstrates the importance of this tool as a complement in dermatological care in our country, especially for patients from regions other than the metropolitan. © 2023 Elsevier España, S.L.U.